2022
DOI: 10.3389/fneur.2022.827749
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Auricular Vagus Nerve Stimulation Modulates the Prefrontal Cortex in Chronic Insomnia Patients: fMRI Study in the First Session

Abstract: ObjectivesTranscutaneous auricular vagus nerve stimulation (taVNS) has been reported to be effective for chronic insomnia (CI). However, the appropriate population for taVNS to treat insomnia is unclear.MethodsTotal twenty-four patients with CI and eighteen health controls (HC) were recruited. Rest-state functional magnetic resonance imaging (Rs-fMRI) was performed before and after 30 min' taVNS at baseline. The activated and deactivated brain regions were revealed by different voxel-based analyses, then the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Correspondingly, the present review suggested that acupuncture could modulate a wide range of FPN regions, including SFG, mPFC, MFG. Acupuncture has been extensively explored for its capacity to alleviate pain by modifying the dysfunctional DLPFC (He et al, 2022 ; Liu et al, 2022 ; Zhang et al, 2022 ). Consequencely, Ong's team revealed the importance of PFC during placebo analgesia and in establishing a connection between pain and pain alleviation in bouts of cognitive performance, anxiety, and cognitive decline (Ong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, the present review suggested that acupuncture could modulate a wide range of FPN regions, including SFG, mPFC, MFG. Acupuncture has been extensively explored for its capacity to alleviate pain by modifying the dysfunctional DLPFC (He et al, 2022 ; Liu et al, 2022 ; Zhang et al, 2022 ). Consequencely, Ong's team revealed the importance of PFC during placebo analgesia and in establishing a connection between pain and pain alleviation in bouts of cognitive performance, anxiety, and cognitive decline (Ong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, although various studies using a pre–post design without a control condition report strong effects of taVNS on insomnia symptoms (He et al, 2022 ; Wu et al, 2021 ; Zhang et al, 2021 ), current evidence from sham‐controlled trials does not indicate substantial effects of taVNS on improving insomnia symptoms.…”
Section: Resultsmentioning
confidence: 85%
“…A possible explanation is that they share some diagnostic symptoms, such as sleeping problems, difficulty concentrating, being easily fatigued, and psychomotor agitation ( 144 ). It has been reported that taVNS treatment is effective in improving sleep quality and prolonging sleep duration in primary insomnia patients via the regulation of a broad brain network (i.e., default mode network, salience network and sensorimotor network) ( 96 , 97 , 145 , 146 ). He and colleagues ( 97 ) have also reported that 4 weeks of taVNS treatment improved chronic insomnia symptoms by decreasing Pittsburgh Sleep Quality Index (PSQI) and Flinders Fatigue Scale (FFS) scores, and increasing the reduced neuroexcitability of the dorsolateral prefrontal cortex.…”
Section: Potential Tavns Effects On Clinical Symptomsmentioning
confidence: 99%
“…It has been reported that taVNS treatment is effective in improving sleep quality and prolonging sleep duration in primary insomnia patients via the regulation of a broad brain network (i.e., default mode network, salience network and sensorimotor network) ( 96 , 97 , 145 , 146 ). He and colleagues ( 97 ) have also reported that 4 weeks of taVNS treatment improved chronic insomnia symptoms by decreasing Pittsburgh Sleep Quality Index (PSQI) and Flinders Fatigue Scale (FFS) scores, and increasing the reduced neuroexcitability of the dorsolateral prefrontal cortex. Altered dorsolateral prefrontal cortex excitability was associated with symptom improvements and may therefore predict the efficacy of taVNS treatment effects.…”
Section: Potential Tavns Effects On Clinical Symptomsmentioning
confidence: 99%